A STUDY ON LOYALTY AMONG PRIVATE SECTOR EMPLOYEES AND ITS DETERMINANTS - Prabhu, M; Madan Mohan, G (Journal of Management Small and Medium Enterprises (SMEs), 2025)
Employees with high loyalty or morale are precious to any firm. This descriptive study has attempted to assess the degree of loyalty prevalent among private-sector employees in Iraq and how such loyalty is driven by job satisfaction and stress. Primary data has been collected by administering a structured questionnaire to 127 private employees selected using simple random sampling. The study results reveal that the employees surveyed are loyal to their company. 106 of the 127 employees have displayed good loyalty towards their firm, and only 13 have shown signs of disloyalty. The employees surveyed do not exhibit signs of stress. However, the employees have indicated that they encounter tiredness from their job, which is indicative of exhaustion due to work pressure, which results in them finding it a bit difficult to sleep and developing headaches that merit immediate attention and rectification. Keywords: Employees; Job Satisfaction; Loyalty; Stress